Properties of 5-hydroxytryptamine3 receptor-gated currents in adult rat dorsal root ganglion neurones. - Robertson, B. (1991)
1. Responses to 5-hydroxytryptamine (5-HT) were examined on rat dorsal root ganglion (DRG) neurones maintained in tissue cultures, by use of whole cell recording techniques. 2. 5-HT (usually 10 microM) evoked a depolarization associated with an increase in membrane conductance in 40% of DRG neurones. There was a considerable variation in the size and persistence of this response between different batches of cells. 3. The 5-HT response was mimicked by applying the agonists 2-methyl-5-HT (10 microM) and phenylbiguanide (10 microM). Responses were blocked by ICS 205-930 (100 nM), but not by methysergide (0.1-1.0 microM). 4. 5-HT currents could be carried by sodium and caesium ions, but not by choline ions. The amplitude and duration of the 5-HT responses were dependent on the concentration of divalent cations in the extracellular solution: both became greater when calcium and magnesium concentrations were decreased. 5. Staurosporine, a putative antagonist of protein kinases, inhibited responses to 5-HT.